Pengaruh Sistem Informasi Akuntansi Penggajian Terhadap Pengendalian Internal Penggajian: Studi Pada Salah Satu Perusahaan Distributor Spare Part Sepeda Motor - Anisa Septiani; Maulana Yusup; Boy Suzanto; Anton Tirta Komara (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2021)
This study aims to determine the effect of payroll accounting information systems on payroll internal control. This study uses a quantitative approach with a survey approach to employees directly related to the accounting information system at a motorcycle spare part dealer in Badung City with 30 respondents. Using a simple linear regression analysis technique to determine the magnitude of the influence used the influence of the payroll accounting information system on payroll internal control. The calculation results show a positive influence of the payroll accounting information system on internal control of payroll with a total effect of 66.4%. The remaining 33.6% can influence by other factors not examined in the study.